2019
DOI: 10.33737/gpps19-bj-016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis Thin Wall Film Formation with Integrated Discrete and Continuous Phase Simulation Approach

Abstract: Water film will be initiated and formed under the continuous impingement of incoming supercooled droplets, and directly affect the ice formation, which is always vital for the performance and safety of aero-engine. A hybrid algorithm integrating Discrete Phase Model (DPM) and Volume of Fluid (VOF) was established to simulate all the stages from droplet initiation to the film well-formed which can make the numerical simulation of icing more realistic and accurate. The transformation criterion from the particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Later, a multiphase CFD model based on the coupled Lagrangian–Eulerian approach was developed to capture the water‐film formation over the S809 airfoil, and it was found that heavy rain could result in a significant performance loss [6, 7]. Recently, this model was also employed to simulate the process of icing [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, a multiphase CFD model based on the coupled Lagrangian–Eulerian approach was developed to capture the water‐film formation over the S809 airfoil, and it was found that heavy rain could result in a significant performance loss [6, 7]. Recently, this model was also employed to simulate the process of icing [15].…”
Section: Introductionmentioning
confidence: 99%
“…Later, a multiphase CFD model based on the coupled Lagrangian-Eulerian approach was developed to capture the water-film formation over the S809 airfoil, and it was found that heavy rain could result in a significant performance loss [6,7]. Recently, this model was also employed to simulate the process of icing [15]. The research by Guo et al [10] indicated that compared to the airplane airfoils, wind turbine airfoils have highly sensitive angles in the operating range and a larger effect of particles could be obtained through momentum exchange between air and particles.…”
Section: Introductionmentioning
confidence: 99%